Women in Leadership - Wells, Katerina; Fleshman, James W. (Clinics in Colon and Rectal Surgery, 2020)
The role of a surgeon is inherently that of a leader and as women become a larger minority in surgical specialties, the next step becomes greater representation of women in positions of surgical leadership. Leadership is a relationship of granting and claiming wherein society must accept that women are deserving of leadership and women must realize their rightfulness to lead. Implicit gender bias undermines this relationship by perpetuating traditional gender norms of women as followers and not as leaders. Though female representation in academia and leadership has increased over the past few decades, this process is unacceptably slow, in part due to manifestations of implicit bias including discrimination within academia, pay inequality, and lack of societal support for childbearing and childcare. The women who have achieved leadership roles are testament to woman's rightfulness to lead and their presence serves to encourage other young professional women that success is possible despite these challenges.
Keywords: women in leadership; women in academia; implicit gender bias; pay inequality